Kemampuan Pedagogical Knowledge Guru IPA Dalam Memotivasi Belajar Siswa Kelas IX SMPN 17 Kota Jambi - Difia Arisandy; Pinta Murni; Nazarudin (UNIB Press, 2022)
The development of learning in the 21st century has a uniqueness that is different from learning in the previous century. This century requires all learning processes to always use technology. Technology can help motivate students and improve skills such as communication skills, creative thinking, critical thinking, and the ability to solve problems. This study aims to analyze the Pedagogical Knowledgeability of science teachers at SMPN 17 Jambi City and to find out whether the teacher's PK ability affects students' learning motivation. This research was a descriptive qualitative research with data collection tools in the form of questionnaires and documentation. Based on the results of the study, it was concluded that the pedagogic knowledgeability of science teachers with a percentage of 85% in the sufficient category was proven to have an effect on students' learning motivation at SMPN 17 Jambi City with indicators motivated by the student's learning environment responding to the agree category with a percentage of 53.5%. The second indicator is paying attention to the teacher when explaining the material, the most students responding agree with the percentage of 43.3%. The third indicator is doing the task on their own accord which contains 2 items of negative statements, the most students giving a disagree response with a percentage of 34.5%, then positive statements from students giving the most agreeing responses with a percentage of 62.1% and the last indicator being an indicator of enthusiasm and enthusiasm. The persistent in doing assignments, students gave the most responses in the agreed category with a percentage of 35.1%.